Profile of emotional intelligence and spiritual intelligence of adolescents from divorced families - Ahmad Bunayya Irsandef; Taufik Taufik; Netrawati Netrawati (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2018)
This research aims to reveal the emotional intelligence of adolescents from divorced families in terms of self-awareness, self-regulation, self-motivation, empathy, and social skills, and spiritual intelligence seen from the aspects of critical existential thinking, personal meaning production, trancendental awareness, and conscious state expansion. This research is descriptive, with research subjects being adolescents from divorced families in the Padang City, amounting to 30 people. The instrument used was a questionnaire with a Likert scale model. The data obtained were analyzed using percentage techniques. The research findings regarding emotional intelligence show that most adolescents from divorced families in Padang City have moderate emotional intelligence. Based on the aspects of emotional intelligence it was found that most of them had moderate self-awareness, self-regulation, self-motivation, empathy, and social skills. The research findings regarding spiritual intelligence show that most adolescents from divorced families in Padang City have moderate spiritual intelligence. Based on the aspect of spiritual intelligence it was found that most of them had moderate critical existential thinking, personal meaning production, transcendental awareness, and conscious state expansion.